Aplikasi Teknologi Pakan Dan Pengolahan Limbah Ternak Pada Kelompok Peternak Sapi Pedaging Di Kabupaten Bantaeng - Said, Muhammad Irfan; Yuliati, Farida Nur; Hatta, Muhammad (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Feed and animal waste aspects are an important component and become the main problem of beef farmers inBantaeng District. The potential of agricultural and livestock waste is very large, however, until now has not been fullyutilized. The objective of this activity is to increase the capacity of beef farmers to utilize the potential of agricultural andlivestock waste into feed and organic fertilizer products. In addition, it is ?Tri Dharma Perguruan Tinggi?. The ?Ipteksbagi Masyarakat (IbM)? programs become one of the solution to the problem. IbM programs for beef farmers has beenimplemented in Ulugalung village, Eremerasa Sub-district, Bantaeng District, South Sulawesi province. Partners of beeffarmer group involved are Livestock Farmer Group (LFG) "Samaturu" and "Cappa Buri". The method of application oftechnology program was implemented in the form of training program and technology assistance. Some of the technologypackages that have been implemented are: 1) straw ammoniac technology processing, 2) complete silage fermentationtechnology, 3) liquid organic fertilizer manufacturing technology (biourin) and local microorganism manufacturingtechnology (MOL) and 4) Urea Molasses Block (UMB) supplement feeding technology. The results of the activities canincrease the capacity of partner members in processing agricultural and livestock waste as animal feed and organicfertilizer